Nexus between risk factors and financial performance: The case of Ukrainian advertising and marketing companies - Tetiana Zavalii; Serhii Lehenchuk; Nina Poyda-Nosyk; Yana Ishchenko; Oleksandr Hrabchuk (Investment Management & Financial Innovations)
The study aims to examine the impact of risk factors of Ukrainian advertising and marketing companies on their financial performance (ROA and ROE). The study was conducted using ordinary least squares regression analysis based on an examination of the activities of 435 companies in 2022. The total number of risk factors (Risk Total) and the ten most common risk factors (10 fixed risk factors) associated with the activities of Ukrainian advertising and marketing companies, calculated using the YouControl database, were selected as independent variables. 10 fixed risk factors were interpreted as dummy variables, which allowed incorporating qualitative information about risk factors of Ukrainian advertising and marketing companies into regression analysis models. Control variables (company age, company size, financial leverage, population at the place of company registration, and total solvency ratio) were added to enhance the determination level of the models. Of these, the statistically significant ones were Company size, which increases ROA and ROE; Financial leverage, which increases ROE; and Company age, which decreases ROE. Of the 11 independent variables that characterized companies’ risk factors, only three were confirmed to significantly impact financial performance indicators (risk factor “Location in the housing stock” reduces ROA and ROE; risk factor “Frequent institutional changes” increases ROA; risk factor “Found match by full name with a politically exposed person” reduces ROE).